Decomposition of changes in the EU income distribution in 2007-2011 - Alari Paulus; Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2017)
We summarise and decompose changes in the household disposable income distribution in 2007-2011 across 27 EU countries to study the impact of the Great Recession on household incomes and the key factors contributing to it. Using microsimulation techniques and applying the EU tax-benefit model EUROMOD in combination with EUSILC household micro-data, we separate direct (first-order) effects of tax-benefit policy on the income distribution from the effects of changes in household market incomes and characteristics. There is substantial variation in income dynamics between and within countries. We find that in most countries, changes in market income and population characteristics had a poverty- and inequality-increasing effect, while policies were more often poverty- and inequality-reducing. However, there is no clear country-level correlation between the two effects in this period.
Keywords: D31; H23; I38; 330; income distribution; decomposition; tax-benefit policies; European Union